HCF-1 Amino- and Carboxy-Terminal Subunit Association through Two Separate Sets of Interaction Modules: Involvement of Fibronectin Type 3 Repeats - Wilson, Angus C. (American Society for Microbiology, 2000)
When herpes simplex virus infects permissive cells, the viral regulatory protein VP16 forms a specific complex with HCF-1, a preexisting nuclear protein involved in cell proliferation. The majority of HCF-1 in the cell is a complex of associated amino (HCF-1(N))- and carboxy (HCF-1(C))-terminal subunits that result from an unusual proteolytic processing of a large precursor polypeptide. Here, we have characterized the structure and function of sequences required for HCF-1(N) and HCF-1(C) subunit association. HCF-1 contains two matched pairs of self-association sequences called SAS1 and SAS2. One of these matched association sequences, SAS1, consists of a short 43-amino-acid region of the HCF-1(N) subunit, which associates with a carboxy-terminal region of the HCF-1(C) subunit that is composed of a tandem pair of fibronectin type 3 repeats, a structural motif known to promote protein-protein interactions. Unexpectedly, the related protein HCF-2, which is not proteolyzed, also contains a functional SAS1 association element, suggesting that this element does not function solely to maintain HCF-1(N) and HCF-1(C) subunit association. HCF-1(N) subunits do not possess a nuclear localization signal. We show that, owing to a carboxy-terminal HCF-1 nuclear localization signal, HCF-1(C) subunits can recruit HCF-1(N) subunits to the nucleus.